Law Enforcement on Child Sexual Abuse in Manado City - Rimbing, Nontje; Sondakh, Meiske T.; Worang, Eske N. (Asia Pacific Journal of Management and Education (APJME), 2021)
This study investigates child sexual abuse cases that remain high in Manado as well as its law enforcement against the perpetrators, especially for underage perpetrators. By using a normative legal method, this research paper aims to examine legal materials, namely the Criminal Code and the Child Protection Law No. 35 of 2014 by collecting empirical data about law enforcement by the North Sulawesi Regional Police. The findings indicate that the law enforcement on underage perpetrators depends on the investigators in charge, in principle, under Law no. 35 of 2014, and they are detained in Child Care Centers of Tomohon. Also, this research specifically underlined that law enforcement against underage perpetrators has followed the procedures of the juvenile justice system, while the victims do need special attention of institutions outside the police. To ensure the rights to education in detention, this study suggests to make special rules regarding the obligation of teachers to provide private lessons.